Clinical Forms of Tuberculosis in Children with Somatic and Infectious Pathologies - M. A. Romanova; A. V. Mordyk; E. S. Leontieva (LLC "Diagnostics and Vaccines", 2016)
The analysis of influence of difference pathology at children on structure of clinical forms of tuberculosis will allow to create approaches to prophylaxis of tuberculosis. Our retrospective research included 1165 children from 0 to 14 years with tuberculosis. Predisposition to development of tuberculosis of respiratory organs in children with the accompanying infectious pathology (90,3%) and with a combination infectious and somatic (93,6%) (χ²= 16,161, р = 0,000). The children with the isolated somatic pathology had the lowest indicators of a lesion of respiratory organs tuberculosis (84%). Extrapulmonary tuberculosis is bound to existence of somatic pathology (8%) (χ²= 9,598, р = 0,029).